2018
DOI: 10.1016/j.numecd.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Disease trends over time and CD4 + CCR5 + T-cells expansion predict carotid atherosclerosis development in patients with systemic lupus erythematosus

Abstract: Serial clinical evaluations over time, rather than a single point estimation of disease activity or CVRF burden, are required to define the risk of carotid atherosclerosis development in SLE patients. Specific T cell subsets are associated with long-term atherosclerotic progression and may further be of help in predicting vascular disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 62 publications
5
17
0
Order By: Relevance
“…This creates a stark difference of atherosclerosis between patients with SLE and healthy controls even when similar Framingham risk factors are shared (54). A prospective study with a 5-year follow-up showed that 32% of SLE patients had atherosclerosis, whereas 4% of the healthy controls developed atherosclerosis (55). Neutrophils have been implicated as mediators of vascular damage with proinflammatory neutrophils promoting endothelial leakage through degradation of the extracellular matrix components, which in turn allows for endothelial dysfunction (56).…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…This creates a stark difference of atherosclerosis between patients with SLE and healthy controls even when similar Framingham risk factors are shared (54). A prospective study with a 5-year follow-up showed that 32% of SLE patients had atherosclerosis, whereas 4% of the healthy controls developed atherosclerosis (55). Neutrophils have been implicated as mediators of vascular damage with proinflammatory neutrophils promoting endothelial leakage through degradation of the extracellular matrix components, which in turn allows for endothelial dysfunction (56).…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…T-cells are major drivers of SLE pathogenesis [26]. Imbalances between effector and regulatory T-cell functions can account for disease flares and for accelerated vascular injury [27].…”
Section: Accelerated Atherosclerosismentioning
confidence: 99%
“…In accordance with a unique pathophysiological background, patients with SLE show a distinctive pattern of vascular injury characterised by focal, rapidly growing and highly unstable lesions rather than generalised vessel wall thickening [39][40][41][42]. Plaque formation in SLE may represent an accelerated mis-repair response to a primary vascular injury, possibly favoured by concomitant "surges" in cellular and humoral inflammatory mediators (perhaps linked to disease flares) as well as in oxidative stress [27,40,43]. In addition, the vascular damage in SLE not only involves large arterial vessels, but also the microcirculation, thus further enhancing the risk of ischemic events [44].…”
Section: Accelerated Atherosclerosismentioning
confidence: 99%
“…It is generally accepted that globally AS causes increased morbidity and mortality [ 1 , 2 ]. Studies have shown that AS plaque is characterized by the accumulation of immune cells such as T-cell [ 3 , 4 ], monocyte/macrophages [ 5 ], dysfunctional endothelial cells (ECs) with endothelial-to-mesenchymal transition (EndMT). EndMT is a physiological process by which ECs develop mesenchymal phenotype to promote growth and development of vital organ such as the heart [ 6 , 7 ] and vascular smooth muscle cells proliferation, migration characterized by expression adhesion molecule Endothelial Selectin ( E -selectin), vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perpetual migration of monocytes and formation of macrophages promote secretion of chemokines such as MCP-1, 2, CXCL1,2,3 etc. which accelerate the recruitment of monocyte/macrophage leading to the formation of advanced vulnerable plaques susceptible to rapture enhancing thrombosis [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%